2015
DOI: 10.3998/jmmh.10381607.0009.104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Postpartum Depression in Middle Eastern/Arab Women

Abstract: Minimal research is available on postpartum depression (PPD) in women from the Middle East/Arab countries. A literature search revealed only 21 empirical studies conducted in the Arab world in the last 20 years. This paper attempts to analyze the existing data for prevalence and risk factors associated with PPD in the target population. The results of review are discussed with implications for prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 60 publications
1
38
2
Order By: Relevance
“…Specifically, 379 there were no studies of women living in low-income Arab countries, despite their greater vulnerability 380 to mental ill health, as compared to women living in middle-or high-income countries. 1,5 There was a 381 skewed focus on depression, with very little research on stress, anxiety or other psychological 382 morbidities, and the large majority of existing studies focused on postnatal mental health with very few 383 studies assessing prenatal mental health. Finally, the nature of social support that was measured in the 384 retrieved articles was limited primarily to familial, including spousal, support with little research 385 examining the support of other family members or close relationships outside the family, and most did 386 not delve into the nature of the support provided.…”
Section: Discussion 337mentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, 379 there were no studies of women living in low-income Arab countries, despite their greater vulnerability 380 to mental ill health, as compared to women living in middle-or high-income countries. 1,5 There was a 381 skewed focus on depression, with very little research on stress, anxiety or other psychological 382 morbidities, and the large majority of existing studies focused on postnatal mental health with very few 383 studies assessing prenatal mental health. Finally, the nature of social support that was measured in the 384 retrieved articles was limited primarily to familial, including spousal, support with little research 385 examining the support of other family members or close relationships outside the family, and most did 386 not delve into the nature of the support provided.…”
Section: Discussion 337mentioning
confidence: 99%
“…8 Studies have also shown spousal 86 support, or family support in general is protective against the development of depression during 87 pregnancy. 1 The "Arab World" is a term used to describe the twenty-two countries that form the Arab League 91 spanning the northern and northeastern parts of Africa and southwest Asia. The region is home to 92 almost 400 million inhabitants, the large majority of whom identify as Arab and Muslim.…”
Section: Social Resources For Empowerment and Their Link To Mental DImentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of postpartum stress continues to increase. The rate of postpartum depression is (18.6%), anxiety (13.1%) and stress (8.7%) (14).…”
Section: Introductionmentioning
confidence: 99%